PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMA PERTIWI 1 PADANG - Marina Elfera; M. Giatman; Yuliarma; Joni Mardizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem examined in this study is the sub-optimal performance of teachers at SMA Pertiwi 1 Padang. This is indicated by the fact that the realization of teacher performance has not yet met the planned targets, which is caused by the sub-optimal leadership of the school principal. This study consists of two variables: the school principal's transformational leadership style (X) and teacher performance (Y). The objectives of this research are to obtain a description of the school principal's transformational leadership style, to obtain a description of the level of teacher performance, and to determine whether there is an influence of the school principal's transformational leadership style on teacher performance. The method used in this research is the explanatory survey method. The data collection technique is through distributing questionnaires using a Likert scale model, which is analyzed using simple regression. The population is 58 teachers at SMA Pertiwi 1 Padang. The data analysis technique used is simple linear regression test. Based on the research results, it was found that the school principal's transformational leadership style is in the effective category and teacher performance is in the moderate category. Furthermore, the data obtained has a linear pattern. The hypothesis test results show that the school principal's transformational leadership style has a positive influence on teacher performance at SMA Pertiwi 1 Padang.